Transformation of Education Management System and Education Administration in Finland - Supala, Supala (EDUMALSYS Journal of Research in Education Management, 2023)
This article discusses the near future of education systems from a planning and administrative perspective. It is thought that the interests of education bind the education system in such a way that no major upheaval is seen. These changes are considered to be the result of the activities of external and internal groups. Thus, attempts were made to draw a caricature picture of the current ideology of education. Another way to look at the direction of change is the position of international education policy. Despite the fact that the change is essentially considered a reformulation, the article concludes that changes in educational administration are possible. Improved market governance and self-governance are thought to have occurred to some extent, but the deregulation of bureaucratic governance and its consequences remains an open question. Finally, appropriate adult schools and educational institutions as organizations and strategies for their development are examined. According to the article, the question of what kind of organization the school is is diverse. In Finnish discourse, the harmonious and open nature of schools may have been exaggerated. The article concludes with a conclusion about the need for changes in educational administration and the importance of studying municipal education administration.